Beginning Object-Oriented Programming with VB 2005 From Novice to Professional - Clark, Daniel R.; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
Beginning Object-Oriented Programming with VB 2005 is a comprehensive resource of correct coding procedures. Author Daniel Clark takes you through all the stages of a programming project, including analysis, modeling, and development, all using object-oriented programming techniques and Visual Basic .NET. Clark explores the structure of classes and their hierarchies, as well as inheritance and interfaces. He also introduces the .NET Framework and the Visual Studio integrated development environment, or IDE. A real-world case study walks you through the design of a solution. You can then transform the design into a functional VB .NET application. The application includes a graphical user interface (GUI), a business logic class library, and integration with a back-end database. Throughout the book, you'll explore the fundamentals of software design, object-oriented programming, Visual Basic .NET 2.0, and the Unified Modeling Language (UML).
Object-Oriented Programming and Design Fundamentals -- Overview of Object-Oriented Programming -- Designing OOP Solutions: Identifying the Class Structure -- Designing OOP Solutions: Modeling the Object Interaction -- Designing OOP Solutions: A Case Study -- Object-Oriented Programming with Visual Basic -- Introducing Visual Basic and the .NET Framework -- Creating Classes -- Creating Class Hierarchies -- Implementing Object Collaboration -- Working with Collections -- Developing Applications with Visual Basic -- OSO Application Revisited: Implementing the Business Logic -- Developing Windows Applications -- Developing Web Applications -- Developing and Consuming Web Services -- Wrapping Up and Reviewing.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books